A sneak peek on Takotsubo Syndrome. (26th April 2021) - Marques Pires, C; Medeiros, P; Oliveira, C; Campos, I; Flores, R; Mane, F; Azevedo, P; Galvao Braga, C; Arantes, C; Antunes, N; Marques, J
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Takotsubo syndrome (TS) is characterized by transient wall motion abnormality of the left ventricle, which may happen in response to different triggers. AIM: To characterize the population with confirmed diagnosis of TS. METHODS: We analysed retrospectively 129 patients (pts) admitted in our center from 2010 to 2018 with this presumptive diagnosis. 29pts were excluded because TS wasn´t confirmed. For each pt we evaluate clinical characteristics, exams results, inhospital complications and long-term outcomes (minimum FUP of 1 year). RESULTS: The average age was 66 years and 89% were females. Regarding the cardiovascular (Cv) risk factors, 78% had hypertension, 53% dyslipidemia and 19% Diabetes mellitus. In relation to noncardiovascular comorbidities it's important to point out that 32% had psychiatric disorders. The trigger was emotional in 37%, physical in 18%, and unidentifiable in 45%. Concerning the clinical presentation 72% had Killip(K) 1 and 13% K≥3 at admission. The initial electrocardiogram had ST-elevation in 37%, T wave inversion in 64% and a mean QTc interval of 470ms. The mean ejection fraction (EF) by echocardiogram was 37%, with apical ballooning in 83% and at least moderate mitral regurgitation (MR) in 11%. Only 16% had intraventricular pressure gradient. Coronarography revealed absence of obstructive coronary disease in 71% of pts. In addition, 51% of pts underwent cardiac magnetic resonance (CMR), which had an increase usage since 2013. The mean time until the CMR was 14 days, which may explain why only 14% had segmental kinetic changes. It's noteworthy that the mean peak NTproBNP/troponin I ratio was 1, 4 ± 2, 9. We compared the ratio in TS with EF < 40% with the one obtained in a cohort of ST-elevation myocardial infarction (MI) with EF < 40% and found statistically difference (1, 7 ± 3, 8vs0, 01 ± 0, 03; p < 0, 001). Considering inhospital complications, 6% had intracardiac thrombus, 2% acute severe MR, 2% ventricular dysrhythmia and 2% died. During the FUP, 2% had recurrence, 4% had acute heart failure hospitalizations an 17% died. CONCLUSION: Despite increased awareness TS is still poorly recognized. Lack of non-invasive tools for reliable diagnosis obliged the use of coronarography. It's noteworthy that the peak NTproBNP/troponin I ratio may help to differentiate TS from MI and the use of CMR should be encouraged to exclude other causes. Although considered a benign condition, significant in-hospital mobility and 2% mortality was observed.